Immunohistochemical Expression of ROS1 in invasive ductal carcinoma of breast in association with hormonal receptor status and Her2Neu expression - Muhammad Umair; Ahmed Ahson Khan; Nighat Jamal; Akhter Ali Bajwa; Tabish Hassan; Muhammad Umair Khan (Journal of Bahria University Medical and Dental College)
Objective: To determine the frequency of immunohistochemical expression of ROS1 in invasive ductal carcinoma of the breast in relation to hormonal receptor status and HER2 expression.